Application of Failure Mode and Effects Analysis (FMEA) Method in Financial Risk Analysis as ERM Implementation Case Study: PT Prima Hijau Lestari - Pramana , Ndinta Herry; Sintha, Lis; Mangani, Ktut Silvanita (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2025)
This study examines financial risks in the implementation of Enterprise Risk Management (ERM) at PT Prima Hijau Lestari, an outsourcing company in Indonesia, using the Failure Mode and Effects Analysis (FMEA) approach in accordance with ISO 31000:2018. The research was motivated by unstable net profits, client dependency, and regulatory challenges. A descriptive qualitative method was applied through structured interviews and document analysis of financial statements and risk management reports. The findings reveal significant fluctuations in financial risks, particularly accounts receivable, during 2019–2024. To address these risks, management is advised to apply the Fishbone method for root cause analysis, use FMEA to prioritize risks through Risk Priority Numbers (RPN), and strengthen monitoring mechanisms. This study contributes to the academic literature by being among the first to apply ERM and FMEA in financial risk management within the outsourcing sector, an area rarely explored in prior research. Practically, it offers recommendations to improve human resource capacity, strengthen credit policies, and adopt digital risk management tools. The results provide valuable insights for both managerial decision-making and future research on risk governance and financial sustainability in emerging markets.